Reactive Voltage Control of Wind Farm Based on Tabu Algorithm - Ren, Xin; Wang, Hua; Wang, Zhongchao; Wang, Qijiang; Li, Bangxing; Wu, Hao; Yang, Jian; Wang, Wei (Frontiers in Energy Research, 2022)
In view of the fact that current wind farms are mostly multi-wind turbines and it is difficult to accurately control a single wind turbine because of its high dimension in the optimization solution process, the article proposes a reactive power and voltage coordinated control strategy suitable for doubly-fed wind farms. The strategy is mainly divided into three layers. The first is the group layer, which can obtain the reactive power compensation task of the entire group according to the current voltage and voltage indicators of the group collection station. The second is the field layer, in which according to the reactive power compensation tasks issued by the group layer, the reactive power tasks are allocated to each field area based on the tabu search algorithm or the equal margin method. The third is the equipment layer, which allocates equal margins in the area according to the reactive power compensation tasks assigned by the field layer. At the field layer, this article divides 66 wind turbines into five different field areas to solve the reactive power compensation distribution task according to the voltage sensitivity characteristics of the wind turbines on different feeders.